CENP-A is a potential prognostic biomarker and correlated with immune infiltration levels in glioma patients - Yang, Yuan; Duan, Mengyun; Zha, Yunfei; Wu, Zijun (Frontiers in Genetics, 2022)
Background: Centromeric protein A (CENP-A), an essential protein involved in chromosomal segregation during cell division, is associated with several cancer types. However, its role in gliomas remains unclear. This study examined the clinical and prognostic significance of CENP-A in gliomas. Methods: Data of patients with glioma were collected from the Cancer Genome Atlas. Logistic regression, the Kruskal–Wallis test, and the Wilcoxon signed-rank test were performed to assess the relationship between CENP-A expression and clinicopathological parameters. The Cox regression model and Kaplan–Meier curve were used to analyze the association between CENP-A and survival outcomes. A prognostic nomogram was constructed based on Cox multivariate analysis. Gene set enrichment analysis (GSEA) was conducted to identify key CENP-A-related pathways and biological processes. Results: CENP-A was upregulated in glioma samples. Increased CENP-A levels were significantly associated with the world health organization (WHO ) grade [Odds ratio (OR) = 49.88 (23.52-129.06) for grade 4 vs. grades 2 and 3], primary therapy outcome [OR = 2.44 (1.64-3.68) for progressive disease (PD) and stable disease (SD) vs. partial response (PR) and complete response (CR)], isocitrate dehydrogenase (IDH) status [OR = 13.76 (9.25-20.96) for wild-type vs. mutant], 1p/19q co-deletion [OR = 5.91 (3.95-9.06) for no codeletion vs. co-deletion], and age [OR = 4.02 (2.68-6.18) for > 60 vs. ≤ 60]. Elevated CENP-A expression was correlated with shorter overall survival in both univariate [hazard ratio (HR): 5.422; 95% confidence interval (CI): 4.044-7.271; P < 0.001] and multivariate analyses (HR: 1.967; 95% CI: 1.280-3.025; P < 0.002). GSEA showed enrichment of numerous cell cycle-and tumor-related pathways in the CENP-A high expression phenotype. The calibration plot and C-index indicated the favorable performance of our nomogram for prognostic prediction in patients with glioma. Conclusion: We propose a role for CENP-A in glioma progression and its potential as a biomarker for glioma diagnosis and prognosis.